Research of Shift Strategy of Pure Electric Vehicle based on Dynamic Programming - Xu Xin; Niu Zhigang; Wang Yang; Lai Chang (Jixie chuandong)
In order to reduce the energy consumption of pure electric vehicles in actual driving, the gear shift law of the two-speed mechanical automatic transmission is optimized. According to the actual needs of urban, suburban and comprehensive driving cycle in Taiyuan city, the driving motors of the vehicles are matched, and the traditional economic shifting rules are formulated based on the motor efficiency. Then, the optimal gear shifting points under different driving cycle in Taiyuan city are solved by dynamic programming, and the optimal two-parameter shift schedule is discovered. Through Matlab/Simulink modeling and simulation, the energy consumption of the two shifting laws under different Driving cycle is compared. The results show that compared with the traditional economic shift law, the optimized two-parameter shift law can better reduce vehicle energy consumption and improve the endurance mileage.